Is the measurement of serum formate concentration useful in the diagnostics of acute methanol poisoning? A prospective study of 38 patients - Zakharov, Sergey; Kurcova, Ivana; Navratil, Tomas; Salek, Tomas; Komarc, Martin; Pelclova, Daniela (Basic & clinical pharmacology & toxicology, 2015)
The aim of this article was to study the role of serum formate (S-formate) in diagnosing methanol poisoning. A prospective study was undertaken of 38 patients from the Czech methanol mass poisoning in 2012 - median age 51 [interquartile range (IQR) 37-62] years with confirmed methanol poisoning. S-formate was measured enzymatically. The receiver operating characteristics (ROC) curve was used to examine the predictive ability of S-formate. Asymptomatic patients had median S-formate of 1.9 (IQR 1.5-2.4) mmol/L. The median S-formate was 15.2 (IQR 13.9-17.6) mmol/L in symptomatic subjects with visual disturbances, 15.4 (12.1-18.0) mmol/L in subjects with dyspnoea and 15.7 (IQR 12.8-18.5) mmol/L in comatose patients. The differences in serum formate concentrations in symptomatic patients depending on clinical features were not significant (all p > 0.05). Patients with long-term visual sequelae of poisoning had median S-formate of 16.1 (IQR 14.3-19.9) mmol/L; with central nervous system (CNS) sequelae, patients had 15.9 (IQR 14.2-19.5) mmol/L. In lethal cases, the median S-formate was 15.2 (IQR 13.8-15.9) mmol/L. The probability of a poor outcome (death or survival with sequelae) was higher than 90% in patients with S-formate ≥17.5 mmol/L, S-lactate ≥7.0 mmol/L and/or pH <6.87. The ROC analysis showed that the corresponding areas under the curve (AUC) were 0.64 (0.44-0.85 CI 95%) for S-formate, 0.75 (0.56-0.93 CI 95%) for 'S-formate+S-lactate' and only 0.54 (0.38-0.69 CI 95%) for serum methanol, which is lower than for S-formate (p < 0.05). The measurement of S-formate is an important tool in the laboratory diagnostics and clinical management of acute methanol poisoning. S-formate ≥3.7 mmol/L can lead to the first clinical signs of visual toxicity, indicating haemodialysis. S-formate ≥11-12 mmol/L is associated with visual/CNS sequelae and a lethal outcome.
Keywords: ROC Curve; methanol; Humans; lidé středního věku; Predictive Value of Tests; formiáty; Lactic Acid; Female; Area Under Curve; dospělí; lidé; Biomarkers; Poisoning; Adult; biologické markery; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; prediktivní hodnota testů; prognóza; Czech Republic; Hydrogen-Ion Concentration; Methanol; Severity of Illness Index; plocha pod křivkou; Formates; otrava; ROC křivka; Česká republika; Acute Disease; koncentrace vodíkových iontů; mužské pohlaví; kyselina mléčná; akutní nemoc; Prognosis